Best Practice Framework and Principles for Monitoring the Effect of Coastal Development on Marine Mammals - Hawkins, Elizabeth R.; Harcourt, Robert; Bejder, Lars; Brooks, Lyndon O.; Grech, Alana; Christiansen, Fredrik; Marsh, Helene; Harrison, Peter L. (Frontiers in Marine Science, 2017)
As the world’s human population increases along the coastal zone, with major alteration of coastal embayments, increased on-water activities and a plethora of other intrusions into the coastal zone, there is a simultaneous increase in pressures on marine mammals. Growing evidence indicates that many marine mammals are highly susceptible to declines resulting from direct and indirect impacts arising from diverse human activities. Too frequently, assessment of the impact from coastal developments on marine mammals has been inadequate or completely lacking. At worst this has led to catastrophic decline in some populations. Without rigorous ecological assessments along with adaptive management frameworks prior to the initiation of developments, the number of marine mammal populations likely to be adversely impacted will continue to rise. To address these shortcomings, we present a globally applicable best practice framework by; i) describing guiding principles and; ii) reviewing appropriate procedures for assessment and monitoring of impacts of coastal developments on marine mammals. The approach outlined is embedded in Environmental Impact Assessment processes as a means by which decision makers and stakeholders can be informed. Recommendations presented are designed to encourage the application of robust scientific evaluation that applies appropriate survey design with sufficient statistical power to detect changes before trigger thresholds are reached. We emphasise that there is an urgent need to ensure assessments are comprehensive, effective and integrated with monitoring and adaptive management actions in order to minimise or effectively mitigate the impacts of human activities on marine mammal populations.